Channel choice in China: Correlates and determinates of satisfaction and use of government service channels in a survey of Chinese cities. Issue 1 (17th March 2020) - Reddick, Christopher; Zheng, Yueping; Perlman, Bruce
Abstract : Purpose: This paper aims to examine the influence of user characteristics on preference for government service delivery channels. Preferences are understood as citizen use of and satisfaction with digital and traditional government contact modalities. User characteristics are represented by three constructs encapsulating the key elements of citizen features and attitudes. Design/methodology/approach: The constructs are tested on data from a survey of 30 cities in China, resulting in 3, 000 respondents, which asked questions on respondents' use of and satisfaction with traditional modes (hotlines and service center channels) and digital modes (e-government and m-government channels) as well as respondents' sociodemographics, technological capacity and view of government. Findings: The results showed two important findings. First, service channel use was related to the first and second constructs (sociodemographics and technological capacity). Second, service channel satisfaction showed strong evidence of relation to the third construct, view of government. Research limitations/implications: The results of this study make an empirical contribution to understanding the features of citizens that influence channel choice for public service contacts. Originality/value: This study contributes to the understanding of channel choice in three areas. First, it is an empirical study using survey data and so adds to a largely case-based and conceptual literature. Second, by looking at the impact of citizen attitudes about government and not just their sociodemographic features. Third, by examining channel choice in the context of a fast-developing country like China.